2022
DOI: 10.1136/bmjopen-2021-048619
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of oral anticoagulants for the treatment of venous thromboembolism in the patients with different renal functions: a systematic review, pairwise and network meta-analysis

Abstract: ObjectivesTo compare the efficacy and safety of direct oral anticoagulants (DOACs) in patients with venous thromboembolism (VTE) and different renal functions.DesignSystematic review containing pairwise and Bayesian network meta-analysis of randomised controlled trials (RCTs).Data sourcesMEDLINE, EMBASE and Cochrane Library.Eligibility criteriaRCTs reporting the efficacy and safety outcomes of DOACs in different creatinine clearance (CrCl) subgroups.Data extraction and synthesisData extraction and quality asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…14 Therefore we feel it will remain a case per case basis whether or not someone should be prescribed anticoagulants post op. Interestingly, a number of medical reviews and NMA have shown that apixaban is associated with the lowest bleeding risk, 15,16 however there is only one randomized trial that utilized apixaban as a strategy for reducing post operative VTE, unfortunately it was not compared with other anticoagulants which would of been very useful as part of our analysis. 17 Another important aspect of thromboprophylaxis post endovenous ablation is recanalization of the treated vein.…”
Section: Discussionmentioning
confidence: 99%
“…14 Therefore we feel it will remain a case per case basis whether or not someone should be prescribed anticoagulants post op. Interestingly, a number of medical reviews and NMA have shown that apixaban is associated with the lowest bleeding risk, 15,16 however there is only one randomized trial that utilized apixaban as a strategy for reducing post operative VTE, unfortunately it was not compared with other anticoagulants which would of been very useful as part of our analysis. 17 Another important aspect of thromboprophylaxis post endovenous ablation is recanalization of the treated vein.…”
Section: Discussionmentioning
confidence: 99%
“…Direct oral anticoagulant agents (DOACs) have been proved to have comparative efficacy and safety profiles as warfarin in reducing the risk of thromboembolic stroke and they are currently widely used in many patient groups. DOACs have been shown to be non-inferior to warfarin in mild to moderate CKD 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from randomized controlled trials of acute VTE treatment with oral anticoagulants have demonstrated very low rates of major bleeding events among individuals with and without CKD. 2 , 6 , 7 , 8 However, because randomized controlled trials tend to include select populations that are closely monitored, they may underreport important safety outcomes compared to what is seen in “real world” practice. Reassuringly, our data on major bleeding is concordant with that reported in seminal randomized controlled trials and some observational studies.…”
mentioning
confidence: 99%